2021
DOI: 10.1186/s12885-020-07748-7
|View full text |Cite
|
Sign up to set email alerts
|

Protocol of the Italian Radical Cystectomy Registry (RIC): a non-randomized, 24-month, multicenter study comparing robotic-assisted, laparoscopic, and open surgery for radical cystectomy in bladder cancer

Abstract: Background Bladder cancer is the ninth most common type of cancer worldwide. In the past, radical cystectomy via open surgery has been considered the gold-standard treatment for muscle invasive bladder cancer. However, in recent years there has been a progressive increase in the use of robot-assisted laparoscopic radical cystectomy. The aim of the current project is to investigate the surgical, oncological, and functional outcomes of patients with bladder cancer who undergo radical cystectomy c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Although past studies have suggested that outcomes are similar among patient who undergo robotic and laparoscopic RC, some of these differences may be due to preoperative differences be-tween groups ( 21 , 22 ). Currently, one study is attempting to disentangle what may be due to inherent differences versus technique in a randomized comparative effectiveness trial ( 24 ). However, it must be noted that surgeons must evaluate the safest and most effective technique for the patient based on a myriad of real-world factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although past studies have suggested that outcomes are similar among patient who undergo robotic and laparoscopic RC, some of these differences may be due to preoperative differences be-tween groups ( 21 , 22 ). Currently, one study is attempting to disentangle what may be due to inherent differences versus technique in a randomized comparative effectiveness trial ( 24 ). However, it must be noted that surgeons must evaluate the safest and most effective technique for the patient based on a myriad of real-world factors.…”
Section: Discussionmentioning
confidence: 99%
“…The Italian Radical Cystectomy Registry (RIC) is an observational, prospective, multi-center, cohort study, assessing patients affected by bladder neoplasms undergoing radical cystectomy and urinary diversion via open, laparoscopic, or robotic-assisted technique ( 24 ). Both male and female consecutive patients are enrolled.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the SEER database lacks specific information about surgery and chemotherapy. The sequence of chemotherapy and the choice of surgical methods and chemotherapy drugs may have different effects on the prognosis ( 25 27 ). Lastly, even if we carried out external validation, further prospective studies were required to verify our conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…The Italian Radical Cystectomy Registry (RIC) is an observational, prospective, multicenter, cohort study, assessing patients affected by bladder neoplasms undergoing radical cystectomy and urinary diversion via open, laparoscopic, or robotic-assisted technique (23). Both male and female consecutive patients are enrolled.…”
Section: Study Design and Inclusion Criteriamentioning
confidence: 99%